PENERAPAN MEDIA PEMBELAJARAN BERBASIS CANVA UNTUK MENINGKATKAN HASIL BELAJAR BIOLOGI SISWA SMA - Putri Rizki Amalia; Maulida Maulida; Syarifah Farissi Hamama (Jurnal Dedikasi Pendidikan, 2024)
This study aims to determine the application of canva-based learning media on human reproductive system material to improve learning outcomes at SMA Negeri 1 Indrapuri. This type of research is pre-experimental with One Group Pretest-Posttest design. The population is all students of class XI IPA SMAN 1 Indrapuri. The sample in this study amounted to 25 people from class XI IPA I. The research instruments used were questions with test techniques to determine the improvement of learning outcomes. Data analysis techniques using N-Gain test and T test to test the hypothesis. The results showed that the learning outcomes of students in class XI IPA 1 before using canva-based learning media were with an average of 38.52 and learning outcomes after using canva-based learning media were with an average of 80.2. The difference between students' pre-test and post-test scores averaged 41.68, and N-gain 0.6656 with a high category. There is an effect of the application of Canva-based learning media for students of class XI IPA SMAN 1 Indrapuri on the Material of the Human Reproductive System with a t-count value greater than the t-table 28,300> 2064. With the results of this study, teachers or educators are expected to choose the use of Canva media as one of the learning media that can improve student learning outcomes, especially on the material of the human reproductive system.